THE POWER OF CHARLIE COMMUNICATION ON ILLOCUTIONARY AND ELLIE RESPONSES ON PERLOCUTIONARY ACTS THROUGH “THE WHALE” MOVIE SCRIPT - Murni, Julia Nada; Rosida, Ana (BASIS (Bahasa dan Sastra Inggris), 2025)
This study aims to find out the illocutionary and perlocutionary acts in the movie The Whale, focusing on the communication between the father, Charlie, and his daughter, Ellie. This research used John Searle's (1979) speech act theory as its theoretical framework. The data source is The Whale movie script, it uses descriptive qualitative research method and note-taking. The findings show 67 utterances of illocutionary acts, with assertive being the most frequent (23 occurrences) and commissive the least (8 occurrences). The most frequent perlocutionary effect was emotive (38 occurrences), while the least frequent was cognitive (8 occurrences). The analysis highlights that Charlie expresses his thoughts honestly, conveying beliefs, hopes, and explanations about his past life. In contrast, Ellie's responses to Charlie's words evoke emotional perlocutionary effects, including anger, frustration, confusion, and cynicism. Their interaction is laden with emotional tension, which illustrates how speech acts shape their complex relationship. This research emphasizes that dialogue serves not only as a means of communication, but also as a powerful tool to reveal deeper meanings, enrich characterization, and provide a stronger emotional experience for the audience.